Zygosaccharomyces rouxii, an Aromatic Yeast Isolated From Chili Sauce, Is Able to Biosynthesize 2-Phenylethanol via the Shikimate or Ehrlich Pathways - Dai, Jun; Li, Ke; Song, Na; Yao, Wanting; Xia, Huili; Yang, Qiao; Zhang, Xiaoling; Li, Xin; Wang, Zhi; Yao, Lan; Yang, Shihui; Chen, Xiong (Frontiers in Microbiology, 2020)
We isolated an aromatic strain of yeast (M2013310) from chili sauce. Assembly, annotation, and phylogenetic analysis based on genome sequencing, identified M2013310 as an allodiploid yeast that was closely related to Zygosaccharomyces rouxii. The genome of this strain was assembled into 38 contigs and 9043 protein-coding sequences were annotated. During fermentation, M2013310, produced an aromatic alcohol with a rose-honey scent; gas chromatography tandem mass spectrometry identified this alcohol as 2-phenylethanol. The concentration of 2-phenylethanol reached 3.8mg/L,1.79g/L, and 3.58g/L, in M3 (NH4+), M3 (NH4++Phe) and M3 (Phe), after 72 h of fermentation, respectively. These data indicate that M2013310 can synthesize 2-phenylethanol via the Shikimate or Ehrlich pathways. However, the mRNA expression levels of ARO8 encoding aromatic aminotransferases I and ARO10 encoding phenylpyruvate decarboxylase by M2013310 in M3 (Phe) were the lowest of the three different forms of media tested. The production of 2-phenylethanol may be significantly improved by the over-expression of these two genes. Our research identified a promising strain of yeast (M2013310) that could be used to improve the production of 2-phenylethanol.